EuGMS survey on structures of geriatric rehabilitation across Europe - Grund, Stefan; Van Wijngaarden, Janneke P.; Gordon, Adam L.; Schols, Jos M.G.A.; Bauer, Jürgen M. (European geriatric medicine, 2020)
The aim of this study is to provide an overview on structures of geriatric rehabilitation across Europe.